Teacher Creativity in Teaching Vocabulary of The 7th Grade Students of SMP Negeri 2 Parepare - Demmanaba, Nopitasari; Patahuddin, Patahuddin; Rahman, Ali Wira (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2023)
The creativity of a teacher in the classroom is very important because it describes the personality of a good teacher, it can also be liked by many people and even by the students being taught. In teaching English, English vocabulary is very important to master in improving fluency in speaking English, increasing understanding and also helping to improve student achievement. The purpose of this study is to determine the creativity of teachers in teaching students' vocabulary, and to determine the effect of teacher creativity on students' vocabulary mastery. Researchers used qualitative research with the case study method. The sample of this research was 1 English teacher and 8 students at 7th grade students. The research instruments in this research were observation, interviews and documentation. This study uses data analysis techniques from Miles and Huberman, namely data collection, data reduction, data display, and data verification. The results of the analysis of the data in this study showed good results between the creativity carried out by the teacher in teaching in class. This is evidenced by the creativity that the teacher always does when learning takes place, the teacher sometimes gives games while learning, gives vocabulary to students to memorize, students are encouraged to use English in class at every meeting, the teacher also always motivates students to always learn English. The increase in English vocabulary is evidenced by how often students use English in class and use English when students meet the teacher.